Implantable cardioverter-defibrillator therapy in the very young - Patient characteristics procedural outcome and one-year follow-up - A subgroup analysis of the german DEVICE registry. (19th May 2022) - Chung, D; Hochadel, M; Senges, J; Kleemann, T; Eckhardt, L; Brachmann, J; Steinbeck, G; Larbig, R; Butter, C; Schulz, E; Willems, S; Hakmi, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The implantable cardioverter-defibrillator (ICD) and cardiac resynchronization therapy defibrillator (CRT-D) are well-established and essential therapeutic pillars for patients with heart failure and survivors of sudden cardiac death. The number of young patients receiving ICD or CRT-D has been increasing in the last decades. Understanding the key differences between the typically older ICD population and younger patients is paramount to optimized patient care. Methods: The DEVICE registry prospectively enrolled patients undergoing ICD/CRT implantation or revision from 50 German centers between 2007–2014. Data on patient characteristics, procedural outcome, adverse events and mortality during the initial stay and follow-up was collected. All patients under the age of 45 years were identified and included into a comparative analysis with the remaining population. Results: A total number of 4181 patients were enrolled into the registry, of which 236 patients (5.6%) were under the age of 45 years. Median age was 38.0 [31.0; 42.0] vs. 69.0 [60.0; 75.0] years, p<0.001), compared to older patients. Young patients were more likely to receive an ICD (91.5 vs. 69.4%, p<0.001), than CRT device and were less likely to suffer from non-cardiac comorbidities (20.3 vs. 67.4%, p<0.001). Coronary artery disease was less common in young patients (15.7 vs. 63.6%, p<0.001), whereas hypertrophic cardiomyopathy (11.0 vs. 2.5%, p<0.001) and primary cardiac electrical diseases (14.0 vs. 1.6%, p< 0.001) were encountered more often. Mean left-ventricular ejection fractions were 42.4±18.5 vs. 31.5±11.8%, respectively (p<0.001) with less young patients in NYHA functional class III/IV (19.5 vs. 45.3%, p<0.001). Primary symptom at presentation was chronic heart failure for older patients (19.5 vs. 34.8%, p<0.001) and survived sudden cardiac death (30.9 vs. 15.6%, p<0.001) for young patients. Thus, ICD for secondary prevention was more common in young patients (53.8 vs. 43.2%, p<0.001). There were no detectable differences in postoperative complications (3.0 vs. 4.1%, p=0.500) or in-hospital mortality (0.0 vs. 0.3%, p=1.000). Median follow-up time was 514 [398; 669] vs. 458 [391; 563] days (p=0.006). Device-associated complications requiring revision were more common in young patients (16.3 vs. 8.2%, p<0.001) and all-cause 1-year-mortality after implantation was lower (3.1 vs. 7.3%, p=0.029; HR 0.42, 95%CI: 0.19-0.94). Even though there was no difference in rates of rehospitalization between groups (32.1 vs. 32.4%, p=0.93), young patients were re-admitted more often for "cardiac" reasons (82.7 vs. 58.9%, p<0.001). Conclusion: Rates for procedural complications and in-hospital mortality were very low and without differences between both age groups. However younger patients experienced a higher rate of postoperative complications requiring revision and had higher readmission rates for cardiac reasons, potentially due to a more active lifestyle.